Municipal Water Supply Systems of Giving-Distributive Complex Reliability with Branched Networks - Novokhatniy, Valeriy; Matyash, Oleksandr; Kostenko, Sergiy (International Journal of Engineering and Technology, 2018)
The basics of the reliability theory of small settlements water supply systems were considered. Methods of the reliability calculation of the supply-distribution complex structures were reviewed: pumping stations, water pipes and branched network. The mathematical reliability model of the water supply technological process to the most distant consumers were constructed according to the water supply selected directions. The real possibility of water supply reliability calculation on an actual example was shown and a graphical representation of the results was performed.Â Â